Debatforum: Ernst Triers Grundtvigresepsjon: Om dannelse og yrkesutdanning i Vallekilde - Walstad, Pål Bødtker (Grundtvig-studier, 2007)
Debatforum[Forum for debate]In the Forum for debate, readers are invited to respond to issues raised, or to raise new issues relative to the field of Grundtvig studies. Items submitted, preferably in the form of an article, may be of any reasonable length and in any of the languages usually accepted by the journal. Contributions in Grundtvig-Studier 2007 are written by Ove Korsgaard and Pål Bødtker Walstad.Unfortunately, due to a mistake during the editing of Professor, dr. p.d. Ove Korsgaard’s contribution “ Hvordan erindres folkehøjskolens historie?” in Grundtvig-Studier 2006, certain sections were misplaced. As this may have caused confusion to the readers, we are reprinting the contribution in its original form. The editors of Grundtvig-Studier 2006 would like to apologise for the misprint. Debatforum: Ernst Triers Grundtvigresepsjon: Om dannelse og yrkesutdanning i Vallekilde[Forum for debate: Ernst Trier ’s Grundtvig reception: On general and vocational education at Vallekilde]By Pål Bødtker Walstad In 1865 Ernst Trier, a young Danish theologian with a close relation to Grundtvig, established Vallekilde Folk High School. He developed a broad range of occupational education units, covering farming, seamanship and fishing, painting and arts, and, especially with the help of the carpenter and teacher Andreas Bentsen, Vallekilde Folk High School offered a variety of education within the field of crafts. Trier strove to maintain all the occupational education units among Vallekilde’s activities. Since, as he believed, each pupil was created in the image of God and therefore a unique human being, Trier wanted his school to “match” the individualities of the pupils. Grundtvig’s expression “ Education and Proficiency for Life” (“ Dannelse og Duelighed for Livet”) was by Trier interpreted as a folk high school including general as well as vocational education.